Altruistic Leadership and Organizational Citizenship Behavior: Mediating Role of Leader-Member Exchange - Bismil One Chanko; Adi Rahmat (SAINS ORGANISASI, 2022)
This study aims to investigate and explain theoretically and empirically the impact of altruistic leadership on employee OCB. Furthermore, this study aims to investigate the psychological mechanisms that influence the relationship. Explanatory studies are used in this study. Using quantitative methods to test hypotheses empirically. This study seeks to obtain data by sending a questionnaire to one of the Regional Apparatus Units (SKPD) in the Pekanbaru city, namely the Pekanbaru City Civil Service Police Unit by utilizing self-administered questionnaire. From the results of questionnaires that have been distributed to 203 members of the Pekanbaru City Civil Service Police Unit, it can be obtained an overview of gender, age, last education, length of service, and achievements. These results are expected to provide innovation and information for leaders to improve relations with subordinates with the aim of advancing the Pekanbaru City Civil Service Police Unit as an enforcer of Regional Regulations and Regional Head Regulations.